Language Feminisation in Sociopolitical Space of Russia and France - L. A. Ulianitckaia (Дискурс, 2020)
Introduction. The paper reviews dynamics of language feminisation and inclusive writing emergence in the context of social change in Russia and France, identification of common patterns for the languages of the countries, adaptation difficulties of new elaborated spelling and punctuation rules, as well as indentification of sources of resistance to gender reforms in languages considered. The relevance of the study is conditioned by the growing interest of sociolinguists to the issues under consideration and by the importance of scientific record of changes in Russian and French against the backdrop of gender processes of recent years (the analysed material covers the period from 2017 to 2020). The features of direct correlation between social and language changes are reviewed not only within the context of language feminisation and feminism relationship, but also regarding historical aspects.Methodology and data sources. The study was conducted using the materials of French and Russian Internet articles, legal acts gouverning gender linguistic issues in France, statistical research data, explanatory and etymological dictionaries, Russian National Corpus, inclusive writing Instructional materials, video footages, official statements, interviews. During the selection of language material continuous sampling technique was applied; the analysis of the instances was carried out using both synchronic and diachronic approaches, allowing to look at the historical development of the languages in terms of containing feminitives. The study of language processes is carried out within the framework of sociolinguistic approach. The main methodology of language feminisation and inclusive writing study included comparative, descriptive, stylistic, and semantic- syntactic analysis.Results and discussion. The main result of the study is a review of the gender linguistic features of French and Russian. The collected and analysed language material allowed to draw the conclusion about an ongoing predominance of masculine grammatical gender over feminine in cases where using feminine grammatical gender would be reasonable and logically sound. Legal acts gouverning the use of feminitives and inclusive writing were also looked at. An inconsistency between language norm and current society needs, as well as the existence of misconception of feminist movement within society and misinterpretation of its objectives, including those related to language feminisation, are identified.Conclusion. Language is a social phenomenon that provides members of society with successful communication. Over the years people have been observing language changes that may have at first be prejudiced or may have faced rejections, but relented over time and became imperceptible and natural for native speakers. The feminisation of language is a logical process that meets civil, political and personal needs of 21st century people.